2001
DOI: 10.1007/s002680020014
|View full text |Cite
|
Sign up to set email alerts
|

Modern Anesthetic Techniques for Thoracic Operations

Abstract: Continuing advances in anesthesiology enable surgeons to perform more and more complex operations. Nowhere is this relation more important than for the patient undergoing thoracic surgery. Specialized anesthetic techniques including safe lung separation, the maintenance of oxygenation during selective one-lung ventilation, and effective postoperative analgesia allow procedures such as lung volume reduction surgery and lung transplantation to be performed routinely. This paper reviews modern clinical practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 30 publications
0
29
0
6
Order By: Relevance
“…Therefore, guidelines were published in multiple papers and books, many of them based on the studies by Katz et al [13] who found that large tidal volumes produced the highest arterial oxygen tension (PaO 2 ) during OLV, leading to the recommendation that tidal volume during OLV should be as high as in two-lung ventilation (i.e., 8-12 ml/kg) [14]. However, ALI is now known to be a problem after thoracic surgery [15], which may be augmented or ameliorated by the strategies chosen for OLV.…”
Section: Acute Lung Injurymentioning
confidence: 99%
“…Therefore, guidelines were published in multiple papers and books, many of them based on the studies by Katz et al [13] who found that large tidal volumes produced the highest arterial oxygen tension (PaO 2 ) during OLV, leading to the recommendation that tidal volume during OLV should be as high as in two-lung ventilation (i.e., 8-12 ml/kg) [14]. However, ALI is now known to be a problem after thoracic surgery [15], which may be augmented or ameliorated by the strategies chosen for OLV.…”
Section: Acute Lung Injurymentioning
confidence: 99%
“…These recommendations were based on studies showing improved oxygenation with a larger Vt. 1,2 In the last decade, however, two significant changes have impacted the management of OLV: the recognition of OLV-induced acute lung injury (ALI) and the increasing popularity of VATS as a surgical technique. Hypoxemia, previously the primary concern of anesthesiologists during OLV, has become less frequent due to improved lung isolation, newer anesthetic agents, and better ventilation management.…”
Section: Objectives Of This Continuing Professional Development (Cpd)mentioning
confidence: 99%
“…Atelectasis formation has been demonstrated to be connected with decreased arterial oxygen tension of more than 50 % and increased intrapulmonary shunt of [11 % during OLV [45]. Therefore, a traditional approach to mechanical ventilation during OLV [46,47] included the application of relatively high tidal volumes in the range of 10-12 ml/kg with zero PEEP in the dependent ventilated lung to maintain hypoxic pulmonary vasoconstriction and thus to overcome hypoxemia during OLV.…”
Section: One-lung Ventilation (Olv)mentioning
confidence: 99%